Joint auditor pair, joint auditor tenure and corporate behavior: evidence / Ali R. Almutairi - Almutairi, Ali R. (Universiti Teknologi MARA Cawangan Selangor, 2016)
This paper investigates the effect of joint auditor pair and joint auditor tenure on corporate behavior. Using a sample of 208 year-observations of public companies traded on the Kuwait stock exchange (KSE) over the period of 2008 to 2009, evidence indicates a positive association between the choice of Big 4-Big 4 (BB) auditor pair and the level of corporate behavior. This result is consistent across the three aspects of corporate behavior (i.e. trading history, communication and disclosure). However, the choice of other auditor pairs has no impact on the company's behavior. In addition, corporate behavior is positively related to joint auditor tenure when joint auditor tenure is measured in a continuous form. Using binary indicators for joint auditor tenure, the results, in general, indicate that corporate behavior in terms of trading history and communication improves after the fifth year of auditor engagement.